Decreased fertility in poor responder women is not related to oocyte morphological status - Nichi, Marcilio (2011)
Introduction: In women showing impaired fertility, a decreased response to ovarian stimulation is a major problem, limiting the number of oocytes to be used for assisted reproduction techniques (ART). Despite the several definitions of poor response, it is still a matter of debate whether young poor responder patients also show a decrease in oocyte quality. The objective in this study was to investigate whether poor ovarian response to the superstimulation protocol is accompanied by impaired oocyte quality.Material and methods: This study included 313 patients younger than 35 years old, undergoing intracytoplasmic sperm injection. Patients with four or fewer MII oocytes (poor-responder group, PR, n = 57) were age-matched with normoresponder patients (NR, n = 256).Results: A higher rate of oocyte retrieval and a trend towards an increase in MII oocyte rate were observed in the NR group when compared to the PR group (71.6 +/- 1.1% and 74.1 +/- 1.0% vs. 56.3 +/- 2.9% and 66.5 +/- 3.7%; p < 0.0001 and p = 0.056, respectively). A trend toward increased implantation rates was observed in the NR group when compared to the PR group (44 and 24.5 +/- 2.0% vs. 28.8 and 16.4 +/- 3.9%; p = 0.0305 and p = 0.0651, respectively).Conclusions: Low response to ovarian stimulation is apparently not related to impaired oocyte quality. However, embryos produced from poor responder oocytes show impaired capacity to implant and to carry a pregnancy to term.